Gut bacteria reflect the adaptation of Diestrammena japanica (Orthoptera: Rhaphidophoridae) to the cave - Dong, Yiyi; Chen, Qianquan; Fang, Zheng; Wu, Qingshan; Xiang, Lan; Niu, Xiaojuan; Liu, Qiuping; Tan, Leitao; Weng, Qingbei (Frontiers in Microbiology, 2022)
The gut microbiota is vital for the nutrition, development, and adaptation of hosts. Diestrammena marmorata, a keystone species in the karst cave in China, functions as a scavenger to supply cave ecosystems with essential energy inputs. It inhabits all parts of cave, regardless of light intensity, however, its morphology is relative with light strengths. Its gut bacteria reflect strategies to adapt to the cave habitat remains unknown. Here we decoded the composition of its gut microbiota by 16S rRNA gene deep sequencing and explored the contribution of gut bacteria to cave adaptation of D. marmorata from three various light zones (light region, weak light, and dark region). We found that gut bacterial communities were composed of 245 operational taxonomic units (OTUs) belonging to nine phyla, with Firmicutes being the most dominating phylum. Although the composition and diversity gut bacterial community of D. marmorata were not significantly different among three light regions, bacterial groups may serve different functions for D. marmorata in differing light strengths. D. marmorata has a lower rate of metabolism in the cave habitats than in light regions. The majority of gut bacteria were likely engaged in nutrition and supplied D. marmorata with essential amino acids. In addition, gut bacteria may play a role in the adaptation of D. marmorata body size. Unveiling the features of the gut bacterial community of D. marmorata would shed light on exploring the roles of gut bacteria in the adaption of hosts to karst cave environments.